(untitled) (Journal of Bangladesh College of Physicians and Surgeons, 2024)
Antivenom has been the cornerstone of management for snake envenomation since its development and clinical use more than 100 years ago. Frequently used antivenoms are polyvalent antibodies, produced by immunizing animals. Like other protein drugs, antivenom has immunogenicity and may cause acute allergic reactions including ‘anaphylaxis’ ranging from mild to life threatening reactions. Premedication with subcutaneous adrenaline has clear benefit evidenced by reduction of number and extent of these events. Due to diversities of venom composition, to be maximally effective, antivenoms should ideally be produced by using the venoms from species of local origin. For ensuring the ongoing safety and effectiveness of this antivenom, routine pharmacovigilance is necessary. Pharmacovigilance is a systematic, scientific study on adverse events that can be reported to concerned authority (Directorate General of Drug Administration (DGDA) in Bangladesh) by active or passive reporting. Introduction of pharmacovigilance will help to improve the monitoring and management of the AV related risks through identification and assessment of suspected drug adverse reactions, ineffectiveness, and other drug-related problems. Bangladesh drug regulatory authority (DGDA) encourages to report adverse events by health professionals following use of AV. At the same time need based distribution of AV and other logistics to the health care facilities across the country has to be established. Health authority should prioritize the need and take necessary actions to produce AV(s) using the venom from the locally collected medically important venomous snakes. Antivenom is an essential drug for managing a community emergency, snakebite envenomation. J Bangladesh Coll Phys Surg 2024; 42: 273-281